A Simulation Study on The Influence of The Call Push-Out Scenarios on Traffic Effectiveness of Multi-Service Network Nodes - Blazej NOWAK (Communications of International Proceedings, 2022)
This paper is devoted to the investigation on   the impact of traffic prioritization mechanisms on the efficiency of multiservice network nodes. In addition, the article presents the most important algorithms and mechanisms used to create the simulation environment used in the research study. The article also contains a variety of research results that show the possibility of evaluating the impact of traffic prioritization mechanisms on the efficiency of a network node.
Keywords: Poznan University of Technology; Poland